Timing of outdoor light exposure is associated with sleep-wake consolidation in community-dwelling older men - Lok, Renske; Ancoli-Israel, Sonia; Ensrud, Kristine E.; Redline, Susan; Stone, Katie L.; Zeitzer, Jamie M. (Frontiers in Sleep, 2023)
A consolidated sleep-wake pattern is essential for maintaining healthy cognition in older individuals, but many suffer from sleep fragmentation that exacerbates age-related cognitive decline and worsens overall mental and physical health. Timed light exposure (light therapy) has been explored as a countermeasure, but mixed results have been obtained. To determine whether the timing of light exposure is important for sleep-wake consolidation, we analyzed the natural light diets of a cohort of community-dwelling older men. The degree of sleep-wake fragmentation and light exposure patterns were obtained over a week using wrist actigraphy. Correlations between fragmentation, light patterns, and various physical and mental health measures were examined (n=877). Our findings revealed that higher sleep-wake fragmentation correlated with poorer physical and mental health and reduced cognition. Moreover, reduced daytime light exposure was associated with increased sleep-wake fragmentation. Interestingly, morning and evening light exposure (>1000 lux) were not useful in distinguishing between low and high sleep-wake fragmentation scores, while increased afternoon light exposure showed much better discrimination. Specifically, optimal discrimination between low and high fragmentation occurred 6.7 hours after habitual sleep offset. This suggests that afternoon light therapy might be more efficient in consolidating sleep and wake in older adults, particularly in those with low-amplitude circadian rhythms. This study highlights the significance of properly-timed light exposure in promoting consolidated sleep and cognitive health among older individuals. Tailored lightbased strategies may have the potential to enhance physical, mental, and cognitive well-being in the aging population.